Challenges to optimising uptake and delivery of a HPV vaccination programme for men who have sex with men - Alice S. Forster; Richard Gilson (Taylor & Francis Group, 2019)
Human papillomavirus (HPV) vaccine programmes targeted at men who have sex with men (MSM) may reduce HPV-related disease burden among this at-risk group in countries where uptake of the vaccine among adolescent girls is sub-optimal and where adolescent boys are not routinely vaccinated. There are challenges to optimising the impact of a MSM programme: ensuring good uptake, understanding the effectiveness of the vaccine in this population and considering the longevity of the programme. Furthermore, monitoring of uptake and ensuring that delivery of the programme does not deprive other aspects of sexual health service resources may present challenges to programme evaluation and delivery. We draw on experience from the UK HPV vaccination programme for MSM, delivered in sexual health and HIV clinics, to better understand these challenges with the aim of supporting the implementation of similar programmes elsewhere in the world.